Study of biomass composition and porosity of raw/torrefied oil palm frond: article - Norazman, Umi Najiha; Matali, Sharmeela; Aziz, Noorhaliza (2017)
In this recent decades, Malaysia face challenges in utilizing fossil fuel as a source of energy. This is due to declining supplies and adverse environmental effects. Therefore, an alternative option has been taken to solve the problem. The renewable energy plays the main role as sources of energy and replace fossil fuel utilization. Among the alternatives, biomass fuels have high tendency and potential in producing the renewable energy which is the fourth most prevalent energy source after coal, oil and natural gases. In this study, the potential of oil palm frond as a biochar feedstock for bio-energy purposes are being explored. Among the properties of OPF to be studied are biomass composition, the characteristics of raw/torrefied oil palm frond (OPF) and other physico-chemical properties. For example, proximate analysis, ultimate analysis and calorific value analysis. Study also is conducted to analyse the porosity of OPF. Proximate analysis was performed via thermogravimetriv analysis [TGA] whereas the biomass composition was determined via Technical Association of Pulp and Paper [TAPPI] method. For the determination of surface area and porosity of OPF, Brunauer Emmer Teller [BET] method is introduced as a method to measure the surface area of oil palm frond. As for elementary analysis, during increasing of torrefaction temperature, the elemental C contents gradually increased and the H and O elements gradually decreased. Then, higher carbon content normally leads to higher calorific value. Raw OPF contained higher volatile matter followed by ash, fixed carbon and moisture content. In raw OPF fibre composition, the highest percentage of lignocellulosic is cellulose (44.17 wt%), followed by hemicellulose (34.83 wt%), lignin (21.00 wt%), and extractives (20.26 wt%). For BET surface area, the surface area will change into different size at a different temperature. As a conclusion, the OPF is observed to be a better feedstock of biomass when subjected to torrefaction, so that it can take place the utilizing of fossil fuel to produce energy and it can possibly replace fossil fuel as an alternative biofuel.